General overview of the tombolos on Turkey's coastlines - (:unkn) unknown (My University, 2012)
Ths paper deals with 11 tombolos, which have hosted urban settlements throughout the long historical process, on Black Sea, Marmara, Aegean and the Medtenanean coastlines in Turkey. Unfo&nately, most of these tombolos that draw attention with their unique appearance within the coastal geomorphology, have not been studied to date. Therefore, this paper alms to make contributions to coastal geomorphology of Turkey. Ths paper provides brief information, not exceedng several paragraphs, about the formation and functional characteristics of tombolos. The fact that this study is a first in Turkey and that the number of tombolos is relatively high prevented from going into details. 2 of the tombolos dealt with in th~sp aper are located on the Black Sea coastline, 2 on the Marmara coastline, 5 on the Aegean coastline and 2 on the Meditenanean coastline. © IDOSI Publications, 2012.
Keywords: Alanya; Arnasra; Belkis; Bodnun; Coastal geomorphology; Sinop